Application of shear wave elastography in the management of thyroid nodules in children and adolescents: our experience and a review of the literature - Borysewicz-Sańczyk, Hanna; Bossowski, Filip; Anikiej, Katarzyna; Sawicka, Beata; Michalak, Justyna; Dzięcioł, Janusz; Bossowski, Artur (Frontiers in Endocrinology, 2024)
Introduction: Shear wave elastography (SWE) is an ultrasound diagnostic method used to measure tissue stiffness. Since the mechanical properties of tissue involved in the pathological process are changed, SWE might indicate regions of the examined tissue covered by the disease. It is well documented, that SWE helps to differentiate benign and malignant nodules in thyroid glands in adults, however, there are still few studies on the application of SWE in thyroid diagnosis in children. The purpose of the study was to assess the application of SWE based on Young's modulus expressed in kPa in the management of thyroid nodules in children and adolescents. Methods: 116 pediatric patients (81 girls and 35 boys) with 168 thyroid nodules were enrolled toin the study and were qualified tofor SWE which was followed by fine needle aspiration biopsy. Results: According to the result of the cytological examination presented in the Bethesda system, nodules were qualified as benign (147 nodules with category II category according to the Bethesda system) and indeterminate or suspicious suspected (21 nodules with category III, IV, and V category according to the Bethesda system). Benign cytological diagnoseis were nodular goitre, parenchymal goitre, nodular colloid goitre, or lymphocytic inflammation. Among indeterminate or suspicioussuspected nodules 15 were diagnosed as III according to the Bethesda system (AUS -Atypia of Undetermined Significance or FLUS --Follicular Lesion of Undetermined Significance in cytology), 1 nodule was diagnosed as IV according to the Bethesda system (suspicious for follicular neoplasm -oxyphilic cell tumor) and 5 as V according to the Bethesda system (suspicious for malignancy). There were no significant differences between TSH and fT4 concentration between benign and suspicious groups. Patients with benign and indeterminate or suspicious suspected thyroid nodules were of comparable age. Mean SWE in benign nodules was statistically significantly lower than in nodules with indeterminate or suspicioussuspected cytology (42.22±16.69 vs. 57.4±24.0 kPa, p=0.0004). 6 patients from suspiciousthe indeterminate or suspicious group were revealed to be malignant in the final histopathological examination. Conclusion: Our results suggest that SWE is a viable diagnostic method, however, it still seems to need some adjustment for pediatric patients.